SOSIALISASI PEMBUATAN LOGO USAHA DAN PENDAFTARAN HAK CIPTA UMKM BINAAN HARGO MANUNGGAL YOGYAKARTA - Wina Driyan Pradana; Ariesta Wibisono Anditya (JOURNAL OF COMMUNITY DEDICATION, 2023)
Socialization on making business logos and copyright registration was carried out because many SMEs shaded by the Hargo Manunggal Yogyakarta SME Communication Forum did not yet register their copyright. Furthermore, there are several SMEs that don't have a business logo at all. This happened due to a lack of education and outreach regarding the importance of logos and copyrights in business. This community service activity was attended by 26 SMEs consisting of the culinary and craft sectors. The program is carried out using a discourse, consultation and demonstration method of how to create an attractive logo and register copyright. The benefit of having a logo and copyright is that SMEs have an attractive identity, add value to the business, are legal and valid so that they cannot be imitated by other businesses. The PKM results show an increase in understanding and awareness of SMEs in creating logos and managing the legality of copyright